Response to Health Crises in Africa: Insight From Executing a 2-Year Project in Nigeria - Muhammad, Aliyu; Ibrahim, Mohammed Auwal; Okoli, Peter Chukwunonso; Sogbanmu, Temitope; Ehilen, Oseghale Emmanuel; Isah, Murtala; Mohammed, Isah Yakub; Animasaun, Isaac Lare; Anjorin, AbdulAzeez; Kenechukwu, Franklin; Ibrahim, Mutiat Bolanle; Ibor, Oju Richard; et al. (My University, 2024)
Science advice aids in integrating scientific evidence into policymaking. In Africa, a significant gap exists between science and policy, necessitating high-quality advisory services. The Multifaceted Response Development from Research on COVID-19 in Africa (MURDER COVID-19) project by the Nigerian Young Academy (May 2021–April 2023) aimed to bridge this gap. Project outputs included eight policy briefs, 10 webinars, a hybrid international conference, and a searchable research equipment database. The project effectively dispelled COVID-19 myths, promoted vaccine confidence, and highlighted the need to strengthen health systems and research capacity. The project provides valuable lessons/recommendations and serves as a model for collaborative initiatives addressing health crises and enhancing research capacity.
Keywords: collaboration; evidence; pandemic; policymakers; science advice; Nigerian Young Academy